Gaya Kepemimpinan Otoriter Yayasan Pendidikan Indonesia Terhadap Kinerja Guru, Staff dan Siswa: Sebuah Systematic Literature Review - Nyayu Hanifah (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to examine the impact of authoritarian leadership style in the Indonesian Education Foundation (YPI) on the performance of teachers, staff, and students through a systematic literature review approach. Authoritarian leadership, often characterized by centralized decision-making and a lack of team participation, can affect dynamics within the educational environment. From the analysis of existing literature, it was found that authoritarian leadership style has diverse impacts on the performance of teachers, staff, and students. On one hand, authoritarian leadership can expedite decision-making and create a clear structure, but on the other hand, this style may reduce motivation and job satisfaction among teachers and staff, while also hindering creativity and student participation in the learning process. Furthermore, the study shows that the relationship between authoritarian leadership style and individual performance in education is highly influenced by the cultural and organizational context. Based on these findings, it is essential for educational institutions to consider adopting a more democratic and participatory leadership style to support the performance and well-being of all involved parties. This study provides valuable insights for the development of a more effective leadership model in the field of education.